PERSEPSI DAN STIGMA PENYANDANG DISABILITAS PADA SISWA-SISWI SEKOLAH MENENGAH ATAS - Ahmad Guntur (LPPMK STIKES Widyagama Husada, 2020)
The People with disabilities can create problems in the school. Schools which have students with disabilities will affect the students around them. Perceptions and stigma are factors in the problems of students, especially schools that accept students with disabilities. The purpose of this study was to analyze the relationship between perceptions and stigma of people with disabilities in senior high school. This study used descriptive correlation design and cross sectional approach with the respondents of senor high school students in Sidoarjo City. The sampling technique used was simple random sampling with sample size of 305 respondents who fill up criteria. The measuring instruments used are self perception with cronbach alpha value of 0.883 and a mental illness scale with cronbach alpha value of 0.783. Bivariate analysis using the chi square test and the result is p value (0.001). So it can be concluded that there is a relationship between perceptions and the stigma of people with disabilities in senior high school.